Psychological Training Programs in Training Periodization: An Effective Strategy to Improve Athlete Performance - Komarudin Komarudin; Geraldi Novian; Alen Rismayadi; Mochamad Yamin Saputra; Mona Fiametta Febrianty; Hafizha Alifa Refitri (Universitas Negeri Jakarta, 2026)
The limited application of psychological aspects in sports training programs is one of the factors that causes athlete performance to be less than optimal, because training has so far focused more on physical, technical, and tactical aspects. This condition indicates a gap between the importance of psychological aspects and its application in the training process, particularly in periodization. This study aims to effect of a psychological training program integrated into training periodization on improving athlete performance. This study used an experimental method with a one-group pretest-posttest design involving 30 athletes and coaches from 10 sports branches using a purposive sampling technique. The research instrument was a closed questionnaire with 20 items administered before and after the treatment. The results showed an increase in the average score from 11.47 to 18.60 and an increase in the percentage of participants from 57% to 93%. The paired sample t-test showed a significance value of .001 (p < .05), indicating a significant effect of the treatment. Thus, a psychological training program in the periodization of training can improve the knowledge and abilities of athletes and coaches, thus becoming an alternative to support improved athlete performance.